Tracking the Evolutionary Trends Among Small-Size Fishes of the Genus Pyrrhulina (Characiforme, Lebiasinidae): New Insights From a Molecular Cytogenetic Perspective - de Moraes, Renata Luiza Rosa; Sassi, Francisco de Menezes Cavalcante; Bertollo, Luiz Antonio Carlos; Marinho, Manoela Maria Ferreira; Viana, Patrik Ferreira; Feldberg, Eliana; Oliveira, Vanessa Cristina Sales; Deon, Geize Aparecida; Al-Rikabi, Ahmed B. H.; Liehr, Thomas; Cioffi, Marcelo de Bello (Frontiers in Genetics, 2021)
Miniature fishes have always been a challenge for cytogenetic studies due to the difficulty in obtaining chromosomal preparations, making them virtually unexplored. An example of this scenario relies on members of the family Lebiasinidae which include miniature to medium-sized, poorly known species, until very recently. The present study is part of undergoing major cytogenetic advances seeking to elucidate the evolutionary history of lebiasinids. Aiming to examine the karyotype diversification more deeply in Pyrrhulina, here we combined classical and molecular cytogenetic analyses, including Giemsa staining, C-banding, repetitive DNA mapping, comparative genomic hybridization (CGH), and whole chromosome painting (WCP) to perform the first analyses in five Pyrrhulina species (Pyrrhulina aff. marilynae, Pyrrhulina sp., P. obermulleri, P. marilynae and Pyrrhulina cf. laeta). The diploid number (2n) ranged from 40 to 42 chromosomes among all analyzed species, but P. marilynae is strikingly differentiated by having 2n = 32 chromosomes and a karyotype composed of large meta/submetacentric chromosomes, whose plesiomorphic status is discussed. The distribution of microsatellites does not markedly differ among species, but the number and position of the rDNA sites underwent significant changes among them. Interspecific comparative genome hybridization (CGH) found a moderate divergence in the repetitive DNA content among the species’ genomes. Noteworthy, the WCP reinforced our previous hypothesis on the origin of the X1X2Y multiple sex chromosome system in P. semifasciata. In summary, our data suggest that the karyotype differentiation in Pyrrhulina has been driven by major structural rearrangements, accompanied by high dynamics of repetitive DNAs.